Placental dysfunction as a basic pathology of perinatal complications - О.V. Kravchenko (Publishing House TRILIST, 2021)
Research aim was to study the features of perinatal complications depending on the nature and timing of therapy in pregnant women with primary placental dysfunction. Materials and methods. 82 pregnant women with verified placental dysfunction (chorionic hypoplasia at 12-13 weeks) against the background of the threat of pregnancy termination and genital tract infections were included. All examined were divided into 2 groups: group I consisted of 42 pregnant women who started treatment before 16 weeks of gestation, group II consisted of 40 pregnant women whose treatment was started after 16 weeks of gestation. Women in group I received micronized progesterone, venotonic Normoven, Magnicum and Artihol. Antibacterial sanitation was carried out before 16 weeks of gestation. Group II also received micronized progesterone only. Antibacterial sanitation in this group was carried out after 16 weeks of gestation. Research results. After antibiotic therapy in group I monoinfections value decreased from 26.8 to 9.5%, mixed infections value decreased from 56.1 to 20.7%, while in group II the effectiveness of antibacterial therapy after 16 weeks was significantly lower. Statistically significant differences in weight, volume and area of the placenta in patients of studied groups were obtained. Assessing perinatal complications showed that the frequency of gestosis, premature birth, intrauterine growth retardation and intrauterine infection of the fetus were almost 2 times less frequent in group I than in group II. Conclusions. Placental dysfunction, which developed in the first trimester against the background of the threat of pregnancy termination and genital tract infections, is the basic pathology for complications of the perinatal period. A timely prescribed set of medical supplies, including micronized progesterone, venotonic Normoven, Artihol and Magnicum, was as an effective method of preventing perinatal complications in pregnant women with primary placental dysfunction. Antibiotic therapy up to 16 weeks of gestation does not fully prevent the development of perinatal complications, but it can significantly reduce the level of severe gestational pathology.